Durability behavior of asphalt mixtures in regard to material properties and gradation type - Ji, Tonggeng; Hao, Peiwen; She, Hongwei; Yang, Kai; Li, Hongxiang; Wang, Dong; Kang, Rui; Liu, Jingwen (Frontiers in Materials, 2023)
The main objective of this study is to compare the differences between different gradation types of mixtures (stone matrix asphalt (SMA), large stone asphalt (LSA), stone asphalt concrete (SAC), and superior performing asphalt pavements (Superpave)) and conventional dense-graded mixtures (asphalt concrete (AC)) in terms of resistance to rutting, moisture damage, low-temperature cracking, and water permeability. The paper reports a study of the effect of different asphalt binders on the performance of asphalt mixtures. The experimental results demonstrated that the gradation types had a significant effect on the engineering performance of asphalt mixtures. SMA20, SAC20, and LSA30 exhibited lower rutting potential than AC20. In addition, SAC20 had a larger stripping ratio, while AC13 had a smaller stripping ratio. The stone matrix asphalt displayed the largest failure strain, while the SAC had the smallest, and Superpave ranged between SMA and SAC. SAC20 had the maximum permeability coefficient, followed by SMA20 and AC20, and Superpave20 had the smallest. The nominal maximum aggregate sizes significantly affected the resistance to permanent deformation, resistance to low-temperature cracking, and moisture sensitivity of the asphalt mixtures. Styrene–butadiene–styrene (SBS)-modified asphalt was found to significantly improve the performance of asphalt mixtures compared with ordinary asphalt.